2020
DOI: 10.1021/acsomega.0c03632
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Nonsolvent-Induced Phase Separation of Cellulose from Ionic Liquid-Based Solutions

Abstract: In the present work, we report for the first time an in-depth study of the factors influencing porous cellulose film structure formation during the nonsolvent-induced phase separation (NIPS) process from biopolymer solutions in ionic liquid-based solvents. The length of the alkyl chain of the ionic liquid’s cation, the solvent/co-solvent ratio, and the type of the cellulose precursor used were found to have great influence both on cellulose solution formation and properties and to the NIPS process with water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…The modified Langmuir model takes into account the influence of concentration of the solute in bulk solution on the desorption process. [ 39 ] For example, this model was successfully used at the evaluation of the adsorption properties against Pb 2+ of cellulose–boehemite films. [ 40 ] The modified Langmuir isotherms obtained with our experimental data are presented in Figure S2, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The modified Langmuir model takes into account the influence of concentration of the solute in bulk solution on the desorption process. [ 39 ] For example, this model was successfully used at the evaluation of the adsorption properties against Pb 2+ of cellulose–boehemite films. [ 40 ] The modified Langmuir isotherms obtained with our experimental data are presented in Figure S2, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the gelation time and the properties of the hydrogels were influenced by the amount of the nonsolvent, silk concentration, and incubation temperature. Recently, Wittmar et al [ 66 ] studied for the first time the NIPS process starting from biopolymer solutions in ionic liquid-based solvents, with or without acetone as a co-solvent, to produce porous cellulose film structures. The results demonstrated that cellulose with a high polymerization degree generated more compact films under identical NIPS conditions, as Figure 4 shows.…”
Section: Phase Separationmentioning
confidence: 99%
“… Influence of the cellulose type on the porous film structure (cross-section of 8 wt % cellulose-based films) [ 66 ]. Reprint with permission from ACS.…”
Section: Figurementioning
confidence: 99%
“…The steady interest towards ionic liquids (ILs) as cellulose and biomass solvent media is supported with such characteristics as their potential recyclability, low vapour pressure, and good chemical and thermal stability [20][21][22][23]. The challenges regarding ILs' high price and high viscosity can be mitigated successfully by the addition of a cosolvent [13,16,21,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%